Implementasi Animasi 2D menggunakan Motion Graphic sebagai Media Informasi Palang Merah Indonesia - Irma Wulandari; Ibrohim Yofid Fananda; Jauari Akhmad Nur Hasim; Aji Sapta Pramulen; Fardani Annisa Damastuti; Ashiliya Atsmara Zukhaha (Bulletin of Computer Science Research, 2025)
The Indonesian Red Cross (PMI) has a significant responsibility in conveying humanitarian information to the public. However, the challenges of effectively communicating information to the broader community remain a primary concern, as conventional media often lack appeal and are difficult to comprehend fully. To address this issue, this study implements 2D animation based on motion graphics as a communication medium for PMI. The animation production process includes creating storyboards, developing visual illustrations, graphic processing, adding motion elements, voice narration, and audio-visual synchronization, resulting in a communicative and engaging medium. 2D animation was chosen because it can present messages with simple yet clear visuals, while motion graphics provide engaging motion dynamics that make information easier to understand and remember. The integration of both allows for the delivery of messages that are concise, interactive, and in line with the characteristics of digital media that are widely accessed by the public. Evaluation results show a significant increase in the level of understanding among respondents after watching the video, with post-test scores reaching 94.8% in the PMI member group and 91.2% in the general public group. These findings affirm that 2D animation media based on motion graphics is effective in enhancing the appeal, understanding, and effectiveness of PMI communication, thus it can be an innovative alternative strategy to expand the reach of humanitarian information.